2012
DOI: 10.1186/1471-2431-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception among Japanese children: an epidemiologic study using an administrative database

Abstract: BackgroundThe epidemiology of intussusception, including its incidence, can vary between different countries. The aim of this study was to describe the epidemiology of childhood intussusception in Japan using data from a nationwide inpatient database.MethodsWe screened the database for eligible cases ≤ 18 years of age, who were coded with a discharge diagnosis of intussusception (International Classification of Diseases, 10th revision: K-561) between July to December in 2007 and 2008. We then selected cases ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
3
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 24 publications
9
42
3
4
Order By: Relevance
“…Recent analyses of childhood intussusception in western countries [13,16,17] have found that the peak age was between 4 and 9 months; the male:female ratio was around 2:1 and PLPs were found in 2.6-15 % of cases, which is essentially consistent with our findings. Our result that the age of pediatric intussusception patients with loss of intestine viability was not significant is in accordance with one earlier study showing that intussusception-associated complications occurred irrespective of patient age [18].…”
Section: Discussionsupporting
confidence: 94%
“…Recent analyses of childhood intussusception in western countries [13,16,17] have found that the peak age was between 4 and 9 months; the male:female ratio was around 2:1 and PLPs were found in 2.6-15 % of cases, which is essentially consistent with our findings. Our result that the age of pediatric intussusception patients with loss of intestine viability was not significant is in accordance with one earlier study showing that intussusception-associated complications occurred irrespective of patient age [18].…”
Section: Discussionsupporting
confidence: 94%
“…Elles représentent moins de 10 % des IIA [10,23,37] mais leur fréquence augmente avec l'âge de l'enfant [10] et sont favorisées par une cause locale, une maladie générale ou un contexte particulier.…”
Section: Invaginations Intestinales Aiguës Secondairesunclassified
“…La surveillance après réduction, pour s'assurer de l'absence de récidive, est effectuée durant une hospitalisation dont la durée varie d'une demi-journée [90] à 48 heures selon les centres [37]. La réalimentation se fera en fonction de la symptomatologie initiale.…”
Section: Traitement Par Réduction Pneumatique Ou Hydrostatiqueunclassified
See 2 more Smart Citations